2011
DOI: 10.1128/aem.03034-10
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces Enable High-Titer Anaerobic 1-Butanol Synthesis in Escherichia coli

Abstract: 1-Butanol, an important chemical feedstock and advanced biofuel, is produced by Clostridium species. Various efforts have been made to transfer the clostridial 1-butanol pathway into other microorganisms. However, in contrast to similar compounds, only limited titers of 1-butanol were attained. In this work, we constructed a modified clostridial 1-butanol pathway in Escherichia coli to provide an irreversible reaction catalyzed by trans-enoyl-coenzyme A (CoA) reductase (Ter) and created NADH and acetyl-CoA dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
508
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 568 publications
(526 citation statements)
references
References 48 publications
12
508
4
2
Order By: Relevance
“…Competing pathways in the host were removed and E. coli atoB was used for formation of acetoacetyl-CoA. The intracellular NADH driving force was further stimulated by employing formate dehydrogenase from C. boidinii [8]. The group also used an ATP driven step to form acetoacetyl-CoA for butanol formation in a cyanobacterium [59].…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Competing pathways in the host were removed and E. coli atoB was used for formation of acetoacetyl-CoA. The intracellular NADH driving force was further stimulated by employing formate dehydrogenase from C. boidinii [8]. The group also used an ATP driven step to form acetoacetyl-CoA for butanol formation in a cyanobacterium [59].…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 99%
“…Some examples illustrating the requirement for cofactor balance and availability include: the conversion of biomass feedstocks containing xylose to ethanol where the formation of xylitol is a problem [1][2][3][4][5][6][7]; as a driving force for more effective production of reduced compounds such as biofuels [8]; in using cytochrome P450s in specific oxidation reactions where the recycling of active enzyme is required [9][10][11]; and the production of chiral pharmaceutical intermediates where specific reductions require a certain cofactor [12,13]. Experimental studies along with more complete computational models have shown a global picture of the flow of reducing equivalents and its connection to cell physiology and allowed these insights to be considered for metabolic engineering purposes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in microbial production of renewable fuels has led to successful synthesis of a variety of next-generation biofuels with improved properties over ethanol 12,14,15,[21][22][23][24][25][26][27] . Microbial synthesis of these reduced chemical species by de novo designed pathways can potentially lead to more efficient production strains, which are necessary for next-generation targets to achieve commercial relevance.…”
mentioning
confidence: 99%
“…[11,12] In another study, NADH accumulation was leveraged as a driving force to boost n-butanol production to 30 g L À1 . [13] An NADH-dependent CoA-reductase, ter, was heterologously introduced to an E. coli strain in which all fermentative NADH-consuming pathways were blocked. A similar study leveraged this ter reductase to reveal the nature of how bottlenecks upstream of crotonyl-CoA affected n-butanol production.…”
Section: N-butanol and Isobutanolmentioning
confidence: 99%
“…Titers improved roughly sixfold by implementing a "pyruvate dehydrogenase bypass" strategy, in which an acetaldehyde dehydrogenase (ald6) and an acetyl-CoA synthetase (acs) were overexpressed in tandem with the NADHdependent CoA reductase (ter). [19] In a more comprehensive study, heterologous expression of the cytosolic pdh gene was demonstrated; when introduced to a strain inhibiting ethanol and glycerol formation, titers of n-butanol were boosted to Batch, 100 h Removal of non-butanol forming fermentative pathways; introduction of ter reductase to produce butaryl-CoA [13] S. cerevisiae n-Butanol 243 mg L À1 Batch, 144 h a) Deletion of adh1; overexpression of mitochondrial keto-acid pathway enzymes [21] E. coli Isobutanol 50 g L À1 Fed-batch, 72 h Gas stripping for in situ product removal [15] S. cerevisiae Isobutanol 1.6 g L À1 Batch, 48 h Deletion of pyruvate decarboxylase; overexpression of enzymes responsible for NADH/NADPH cofactor balance [26] E. coli Extended n-alcohols…”
Section: N-butanol and Isobutanolmentioning
confidence: 99%